2009
DOI: 10.1152/ajpgi.90472.2008
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to enteric neural signaling underlie secretory abnormalities of the ileum in experimental colitis in the guinea pig

Abstract: Hons IM, Burda JE, Grider JR, Mawe GM, Sharkey KA. Alterations to enteric neural signaling underlie secretory abnormalities of the ileum in experimental colitis in the guinea pig. Am J Physiol Gastrointest Liver Physiol 296: G717-G726, 2009. First published February 12, 2009 doi:10.1152/ajpgi.90472.2008.-Inflammatory bowel diseases (IBD) can involve widespread gastrointestinal dysfunction, even in cases in which inflammation is localized to a single site. The underlying pathophysiology of dysfunction in nonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
1
17
0
Order By: Relevance
“…There is biochemical evidence that gut immune cells express cholinergic receptors (Kikuchi et al, 2008) and many studies have shown that the manipulation of the vagus nerve (e.g., by electric stimulation, transection) can significantly impact gut immunity (de Jonge et al, 2005; Ghia et al, 2008; Gottwald et al, 1997; Hons et al, 2009; Luyer et al, 2005). Furthermore, cholinergic innervation to the intestinal mucosa may also regulate ion and nutrient transport across the epithelial barrier, as well as parietal cell secretion, blood flow, and epithelial cell proliferation, all of which could indirectly influence immune cell functions (Dhawan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…There is biochemical evidence that gut immune cells express cholinergic receptors (Kikuchi et al, 2008) and many studies have shown that the manipulation of the vagus nerve (e.g., by electric stimulation, transection) can significantly impact gut immunity (de Jonge et al, 2005; Ghia et al, 2008; Gottwald et al, 1997; Hons et al, 2009; Luyer et al, 2005). Furthermore, cholinergic innervation to the intestinal mucosa may also regulate ion and nutrient transport across the epithelial barrier, as well as parietal cell secretion, blood flow, and epithelial cell proliferation, all of which could indirectly influence immune cell functions (Dhawan et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunction of the bowel is found in non-inflamed regions, as well as in the portions of the gut that display obvious inflammation [49]. This dysfunction is associated with long-lasting changes in enteric neural circuits.…”
Section: Changes In the Ens During Intestinal Inflammationmentioning
confidence: 99%
“…ENS dysfunction caused by inflammation induces secretion, as well as motility, to become abnormal, and even in non-inflamed portions of the intestine. In animals with trinitrobenzene sulfonic acid (TNBS)-induced colitis, non-cholinergic secretion was decreased significantly in the ileum, even though inflammation could not be detected in ileal tissue [49]. This secretory change was associated with a dramatic reduction of slow excitatory synaptic transmission in VIP-expressing secretomotor neurons of the submucosal plexus.…”
Section: Changes In the Ens During Intestinal Inflammationmentioning
confidence: 99%
“…These changes occur at both inflamed and noninflamed sites of the gut and result in secretion and motor abnormalities, which contribute to the wide-ranging clinical symptoms such as abdominal discomfort, bloating, and diarrhea (Blandizzi et al, 2003;Hons et al, 2009). However, the communication between the autonomic nervous system and immune system is bidirectional, and not only inflammatory mediators induce neuronal responses, but also acetylcholine (ACh) and catecholamines modulate directly the functions of macrophages, neutrophils, and lymphocytes (recently reviewed by Di Giovangiulio et al, 2015;Kawashima et al, 2015;Pavlov and Tracey, 2015).…”
Section: Introductionmentioning
confidence: 99%